Changes in pediatric hospital care during the COVID-19 pandemic: a national qualitative study - Nicole Y. Penwill; Nadia Roessler De Angulo; Priya R. Pathak; Clairissa Ja; Martha J. Elster; Daniela Hochreiter; Jacqueline M. Newton; Karen M. Wilson; Sunitha V. Kaiser (BMC, 2021)
Abstract Background The COVID-19 pandemic has necessitated rapid changes in healthcare delivery in the United States, including changes in the care of hospitalized children. The objectives of this study were to identify major changes in healthcare delivery for hospitalized children during the COVID-19 pandemic, identify lessons learned from these changes, and compare and contrast the experiences of children's and community hospitals. Methods We purposefully sampled participants from both community and children's hospitals serving pediatric patients in the six U.S. states with the highest COVID-19 hospitalization rates at the onset of the pandemic. We recruited 2-3 participants from each hospital (mix of administrators, front-line physicians, nurses, and parents/caregivers) for semi-structured interviews. We analyzed interview data using constant comparative methods to identify major themes. Results We interviewed 30 participants from 12 hospitals. Participants described how leaders rapidly developed new hospital policies (e.g., directing use of personal protective equipment) and how this was facilitated by reviewing internal and external data frequently and engaging all relevant stakeholders. Hospital leaders optimized communication through regular, transparent, multi-modal, and bi-directional communication. Clinicians increased use of videoconference and telehealth to facilitate physical distancing, but these technologies may have disadvantaged non-English speakers. Due to declining volumes of hospitalized children and surges of adult patients, clinicians newly provided care for hospitalized adults. This was facilitated by developing care teams supported by adult hospitalists, multidisciplinary support via videoconference, and educational resources. Participants described how the pandemic negatively impacted clinicians' mental health, and they stressed the importance of mental health resources and wellness activities/spaces. Conclusions We identified several major changes in inpatient pediatric care delivery during the COVID-19 pandemic, including the adoption of new hospital policies, video communication, staffing models, education strategies, and staff mental health supports. We outline important lessons learned, including strategies for successfully developing new policies, effectively communicating with staff, and supporting clinicians' expanding scope of practice. Potentially important focus areas in pandemic recovery include assessing and supporting clinicians' mental health and well-being, re-evaluating trainees' skills/competencies, and adapting educational strategies as needed. These findings can help guide hospital leaders in supporting pandemic recovery and addressing future crises.